2009
DOI: 10.1002/jat.1471
|View full text |Cite
|
Sign up to set email alerts
|

Fetal and offspring arrhythmia following exposure to nicotine during pregnancy

Abstract: Although recent studies have demonstrated prenatal nicotine can increase cardiovascular risk in the offspring, it is unknown whether exposure to nicotine during pregnancy also may be a risk for development of arrhythmia in the offspring. In addition, in previous studies of fetal arrhythmia affected by smoking, only two patterns, bradycardia and tachycardia, were observed. The present study examined acute effects of maternal nicotine on the fetal arrhythmia in utero, and chronic influence on offspring arrhythmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…Potentially, cigarette smoking by patrons and employees in back rooms may occur, but no cigarette smoking was observed in the main room of the hookah bars surveyed in this study. In addition to its potential for addiction and as a gateway to the use of other tobacco products, nicotine is known to have myriad harmful health consequences, such as teratogenic effects on neurodevelopment,43 44 ‘altering the formation, survival, and differentiation of brain cells, eliciting deficits in structure, synaptic function and behavioral performance’,45 and alteration in neurotransmitters,46 as well as being associated with fatal arrhythmias,47 low birth weight from prenatal exposure,48 hearing loss,49 tooth decay50 and hyperactivity 51 52…”
Section: Discussionmentioning
confidence: 99%
“…Potentially, cigarette smoking by patrons and employees in back rooms may occur, but no cigarette smoking was observed in the main room of the hookah bars surveyed in this study. In addition to its potential for addiction and as a gateway to the use of other tobacco products, nicotine is known to have myriad harmful health consequences, such as teratogenic effects on neurodevelopment,43 44 ‘altering the formation, survival, and differentiation of brain cells, eliciting deficits in structure, synaptic function and behavioral performance’,45 and alteration in neurotransmitters,46 as well as being associated with fatal arrhythmias,47 low birth weight from prenatal exposure,48 hearing loss,49 tooth decay50 and hyperactivity 51 52…”
Section: Discussionmentioning
confidence: 99%
“…Also exposing pregnant rats to nicotine caused an increase in the secretion of sympathetic neurotransmitters of their newborns and, by suppressing the PKC gene, caused rising of cardiac complications in their embryo [4]. Some other studies have reported the effects of prenatal exposure of rats to nicotine and its associated effects on cardiovascular system such as tachycardia, arrhythmia, ischemia, and atherosclerosis [2730]. Totally, all nicotine exposed groups showed disturbances of the serum levels of all the evaluated inflammatory markers in comparison with the nonexposed group and a dose dependent trend was seen among almost all the evaluated markers in exposed rats.…”
Section: Discussionmentioning
confidence: 99%
“…Embryos were exposed to different concentrations of nicotine solutions (50 µM, 100 µM, and 1.2 mM) and heart rates were measured after 5 min of nicotine exposure. Like cocaine, nicotine exposure showed dose-dependent effect on heart function, causing tachycardia at lower doses and bradycardia at higher doses [34], resembling the types of arrhythmia previously observed in other model organisms [91]. However, chronic exposure to nicotine from 2–48 hpf reduced the heartbeat of embryos at later stages, an effect possibly due to the malformed heart [34].…”
Section: Toxic Substances Causing Heart Defects In Zebrafishmentioning
confidence: 91%